A systematic mutation screen of 10 nuclear and 25 mitochondrial candidate genes in 21 patients with cytochrome c oxidase (COX) deficiency shows tRNA(Ser)(UCN) mutations in a subgroup with syndromal encephalopathy. Issue 11 (November 1998) - Jaksch, M; Hofmann, S; Kleinle, S; Liechti-Gallati, S; Pongratz, D E; Müller-Höcker, J; Jedele, K B; Meitinger, T; Gerbitz, K D
Abstract : COX deficiency is believed to be the most common defect in neonates and infants with mitochondrial diseases. To explore the causes of this group of disorders, we examined 25 mitochondrial genes (three COX subunit genes and 22 tRNA genes) and 10 nuclear COX subunit genes for disease associated mutations using PCR-SSCP and direct sequencing of polymorphic SSCP fragments. DNA from one patient with severe COX deficiency and with consanguineous parents was entirely sequenced. The patient population consisted of 21 unrelated index patients with mitochondrial disorders and predominant (n=7) or isolated (n=14) COX deficiency. We detected two distinct tRNA(Ser)(UCN) mutations, which have been recently described in single kindreds, in a subgroup of four patients with COX deficiency, deafness, myoclonic epilepsy, ataxia, and mental retardation. Besides a number of nucleotide variants, a single novel missense mutation, which may contribute to the disease phenotype, was found in the mitochondrial encoded COX 1 gene (G6480A). Mutations in nuclear encoded COX subunit genes were not detected in this study.